The namesake - Lahiri, Jhumpa (New York : Mariner Book, 2004)
When his Indian immigrant parents give him an odd name, a boy must struggle towards manhood suffering the burdens of this name as well as the conflicting loyalties of his heritage.
Keywords: Young men -- Fiction; Domestic fiction